VD_FINDINFO HC / 2016 / 217 vom 18. Januar 2016 - VD Tribunal cantonal (2016)
DÉCISION INCIDENTE, LITISPENDANCE, INTERNATIONAL, DROIT D'ÊTRE ENTENDU | 114 CC, 101 al. 1 CPC (CH), 101 al. 3 CPC (CH), 131 CPC (CH), 308 al. 1 let. a CPC (CH), 59 al. 2 let. d CPC (CH)